Acquired Hemophilia A in the South of Tunisia: A Single Center Study - FRIKHA, Imen; Hdijji, Sondes; Krichen, Imen; Kallel, Faten; Medhaffer, Moez; Kallel, Choumous; Elloumi, Moez (Archives of Clinical and Medical Case Reports, 2019)
Acquired hemophilia A (AHA) is a rare and severe bleeding disorder characterized by the development of autoantibodies against factor VIII. There is no previous study published in our country for AHA. The aim of this study that to describe the clinical symptoms, diagnostic criteria and treatment strategies in patients with AHA in the south of Tunisia. We retrospectively collected all patients diagnosed with AHA in the Department of Hematology of Hedi Chaker Hospital (Tunisia) from 2000 to 2017. The diagnosis was established in the presence of clinical hemorrhagic features associated with the isolated prolongation of the activated partial thromboplastin time (APTT), not corrected after two hours by incubating patient plasma with equal volumes of normal plasma, and with factor VIII less than 50%. We collected five patients with AHA in the South of Tunisia. There were 4 females and 1 male with the median age of 32 years old. The median FVIII C was 7% and the median value of FVIII inhibitor was 11 UB. The most common clinical symptoms were post-partum hematoma in 3 patients (60%), extensive cutaneous hematoma in one patient and hemorrhagic tooth extraction in one patient. All patients were treated in first-line therapy with bypassing agent FVIIa with successful response in 80% of cases. The first-line treatment of bleeding in AHA requires a bypassing agent and the optimal therapeutic strategy to eradicate the inhibitor include immunosuppression with corticosteroids alone or corticosteroids in combination with cyclophosphamide.